2002
DOI: 10.1080/0307945021000005824
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects of Marek's disease virus (MDV) and herpesvirus of turkeys (HVT) in broiler chickens and the protective effect of HVT vaccination against MDV challenge

Abstract: Much of the impact of Marek's disease in broiler chickens is considered to be due to immunosuppression induced by Marek's disease virus (MDV). The present study evaluates the effects of an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 32 publications
5
35
2
Order By: Relevance
“…However, these immunosuppressive diseases and their subsequent secondary infections often affect commercial chickens. According to previous reports, the co-infection of REV with MDV is common in many countries; however, the mechanism of MDV-or REV-induced immunosuppression has not been fully elucidated (Davidson & Boreshtain, 2001;Islam et al, 2002). Zheng et al (2006) observed that an increase in the incidence of MD in broilers was associated with a simultaneous increase in the incidence of REV in chickens.…”
Section: Naturally Occurring Co-infection Of Avian Leukosis Virus (Sumentioning
confidence: 99%
“…However, these immunosuppressive diseases and their subsequent secondary infections often affect commercial chickens. According to previous reports, the co-infection of REV with MDV is common in many countries; however, the mechanism of MDV-or REV-induced immunosuppression has not been fully elucidated (Davidson & Boreshtain, 2001;Islam et al, 2002). Zheng et al (2006) observed that an increase in the incidence of MD in broilers was associated with a simultaneous increase in the incidence of REV in chickens.…”
Section: Naturally Occurring Co-infection Of Avian Leukosis Virus (Sumentioning
confidence: 99%
“…One of the most interesting additions to the accumulated knowledge for research focusing on controlling infectious diseases has been a better understanding of how the host's immune system recognizes danger signals (Babiuk et al, 2003). The viruses that cause immunosuppressive effects in chickens are oncogenic viruses such as Marek disease virus (MDV), reticuloendotheliosis virus (REV) and avian leukosis virus (ALV), certain respiratory viruses such as infectious laryngiotrachitis virus (ILTV), Newcastle disease virus (NDV), and reoviruses, besides the infectious bursal disease virus (IBDV), chicken anaemia virus (CAV), and adenoviruses (Van den Berg, 1996;Islam et al, 2002), which are of major interest because of the widespread occurrence of the infections in commercial chickens and the severe economic losses they cause.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this disease has a sever immune suppressive nature which may be due to cell cytolysis and lymphomas development (Calnek, 2001). Therefore, MD infection is associated with great economic losses that are related to the cost of vaccination, morbidities, mortalities and the increased susceptibility of the infected birds to other infections as a result of MD induced immunosuppression (Islam et al 2002).…”
Section: Introductionmentioning
confidence: 99%